Purification, Spiritualism, and Reform: Muhammadiyah’s Reception of Neo-Sufism - Bachtiar, Hasnan; Nurhakim, Moh.; Rohim, Fathor (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2025)
This paper aims to explore Muhammadiyah’s engagement with Islamic discourse on Sufism, neo-Sufism, and reform. Muhammadiyah appears to adopt a rather critical stance toward Sufism. This qualitative research study employs a combination of discourse analysis and hermeneutics to outline the organization’s perspective on Islamic spiritualism as a discursive phenomenon. This perspective is analyzed interpretively and enriched by scholarly sources, including its ideological framework, the ideas of its leaders, and its socio-cultural context. We find that Muhammadiyah, which espouses a Salafist-leaning ideology primarily opposed to superstition and heresy, does not reject Sufism outright. We argue that the organization’s reluctance to embrace organized Sufism as a modern Islamic expression aims to prevent misunderstanding among its Muslim constituency, while selectively incorporating discursive elements that align with Shari‘ah and modernity. Consequently, Muhammadiyah is more inclined to accept ideas associated with neo-Sufism. This study acknowledges the possibility of a conceptual reconstruction of thought around textualist and conservative ideas that should not be labeled as anti-Sufi.